2019
DOI: 10.3390/mi10080502
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Three Degrees-of-Freedom Rotary Vibration-Assisted Micropolishing System Based on Piezoelectric Actuation

Abstract: The limited degrees of freedom (DOF) and movement form of the compliant vibration-assisted processing device are inherent constraints of the polishing technique. In this paper, a concept of a 3-DOF rotary vibration-assisted micropolishing system (3D RVMS) is proposed and demonstrated. The 3-DOF means the proposed vibration-assisted polishing device (VPD) is driven by three piezo-electric (PZT) actuators. Compared with the current vibration-assisted polishing technology which generates a trajectory with orthogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The polishing experimental results showed that the MRR was increased by 24.1−33.7%, and as the vibration parameter (amplitude and frequency) increased, the Sa decreased. Gu et al 23 developed a three-degree-of-freedom rotational vibration-assisted micropolishing device (3D RVMS) and applied it to SiC polishing. The results showed that Sa was 0.2 μm without vibration and 0.035 μm with 3D RVMS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The polishing experimental results showed that the MRR was increased by 24.1−33.7%, and as the vibration parameter (amplitude and frequency) increased, the Sa decreased. Gu et al 23 developed a three-degree-of-freedom rotational vibration-assisted micropolishing device (3D RVMS) and applied it to SiC polishing. The results showed that Sa was 0.2 μm without vibration and 0.035 μm with 3D RVMS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yu et al [ 27 ] analyzed the inverse dynamics of the 8R compliant mechanism based on Structural dynamics to model the compliant mechanism. Go et al [ 28 ] proposed a concept of a 3-DOF rotary vibration-assisted micropolishing system (3D RVMS) and determined the dynamic and static performances based on compliance matrix method and FEA. In this paper, we established a complex dynamic model of a 6-DOF platform and considered the damping dissipation in the process of establishing a dynamic model with the Lagrange equation.…”
Section: Introductionmentioning
confidence: 99%